Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/toxins14030162
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Validity of Normalizing Aflatoxin B1-Lysine Albumin Adduct Biomarker Measurements to Total Serum Albumin Concentration across Multiple Human Population Studies

Abstract: The assessment of aflatoxin B1 (AFB1) exposure using isotope-dilution liquid chromatography-mass spectrometry (LCMS) of AFB1-lysine adducts in human serum albumin (HSA) has proven to be a highly productive strategy for the biomonitoring of AFB1 exposure. To compare samples across different individuals and settings, the conventional practice has involved the normalization of raw AFB1-lysine adduct concentrations (e.g., pg/mL serum or plasma) to the total circulating HSA concentration (e.g., pg/mg HSA). It is hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…As an alternative, Dried Blood Spots have shown promise since measured values were normalized by the amount of HSA, not serum volume [ 20 ]. There is recent evidence that suggests that aflatoxin serum adducts should be normalized by serum volume and not by HSA [ 18 ]. This means that unless the volume of serum or blood is carefully applied to a DBS card prior to desiccation and shipping, it may not easily compatible with this analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative, Dried Blood Spots have shown promise since measured values were normalized by the amount of HSA, not serum volume [ 20 ]. There is recent evidence that suggests that aflatoxin serum adducts should be normalized by serum volume and not by HSA [ 18 ]. This means that unless the volume of serum or blood is carefully applied to a DBS card prior to desiccation and shipping, it may not easily compatible with this analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, the amount of HSA in the serum has been quantified to normalize the reported AFB 1 -Lys concentration in units of pg/mg albumin. A recent analysis of a large number of samples from many countries suggested that this normalization step may not be necessary [ 18 ]. Of the various analytical approaches reported, the most reliable data come from liquid chromatography–tandem mass spectrometry methods [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…AFB 1 -lysine adduct concentration presented in this study was not expressed relative to albumin. It has been reported elsewhere that normalizing AFB 1 -lysine adduct concentration to serum albumin is not necessary when the former was measured by IDMS [ 24 ]. We did human serum albumin (HSA) normalization in plasma samples of mothers ( n = 98) collected at baseline and 36 weeks of gestation in this current study to see if normalization would make a difference.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesize that the proteolytic digestion in our AFB1-lys methodology likely addresses any potential interference from the presence of fibrin, and that the presence of the heparin additive itself does not interfere with proteolysis. However, the comparability of heparinized plasma albumin measurements with serum is also needed since an albumin concentration measurement is used by convention to normalize for the circulating albumin concentration from which the AFB1-lys analyte is proteolytically generated [25]. It has been documented that heparin can form insoluble precipitates with the bromocresol green reagent used in the colorimetric determination of albumin and can yield erroneously low results [26,27].…”
Section: Preanalytical Factorsmentioning
confidence: 99%
“…The use of bromocresol purple [26] or additives with bromocresol green [27] has been shown to restore accuracy to heparinized plasma albumin measurements but we have not tested these approaches. The need for normalizing AFB1-lys measurements itself has been called into question [25], and so we believe further evaluation of heparinized plasma for AFB1-lys measurements is worth consideration.…”
Section: Preanalytical Factorsmentioning
confidence: 99%